Comparison of voice quality in patients with oral cancer at both pre and post treatment stage - Sahoo, Lokanath; Thakur, Bandana; Kumar, Manoj; Sharma, Komal; Sasi, Shraddha; Singh, Nitu; Upadhyay, Kiran; Kurkure, Rahul; Sahoo, Krushnendu Sundar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Patients with oral cancer have very common complaints of change in voice. This research is designed to study the effect of oral cancer and its treatment on the various domains of voice like functional, physical, and emotional along with parameters of voice like pitch, loudness and quality. Method: This study included total 48 participants (34 males and 14 females) with oral cancer. The voice quality of the participants was analysed both before and after treatment using Dr. speech and the voice handicap index (VHI). First, the voice analysis done when the patient was diagnosed as a case of oral cancer by the head-neck oncosurgeon after completion of all required investigations. Patients were recalled for voice analysis after completion of treatment. Results: There was a significant difference observed in all three domains of the VHI at both before and after treatment. The difference in the functional domain was more prominent. The VHI was not linked to tumor or nodal staging. However, post treatment the voice parameters are greatly affected as compared to pre-treatment stage. Conclusions: The administration of the VHI should be made mandatory prior to treatment of oral cancer and the findings of the test should be discussed with the patient prior to start of any treatment modality and accordingly the realistic expectations can be set. Therefore, voice analysis using Dr speech will also help in timely assessment and rehabilitation of voice before and after treatment.